Pancreas divisum: case report - Salloum Filho , Eduardo (2021)
Introduction: Pancreas Divisum is an anatomical anomaly of the pancreatic duct in which the majority of the pancreatic juice passes through the smaller papilla and the minority through the larger papilla. Case report: A 54-year-old patient with Pancreas Divisumque was diagnosed with pancreas divisum occasionally during investigation for elucidation of altered liver enzymes and dyspepsia. Discussion: Pancreas Divisum is a poorly addressed entity due to the lack of symptoms in most cases, but there is more recent evidence that this entity could be related to the higher incidence of other pathologies such as pancreatitis and pancreatic tumor. Conclusion: As it is a rare and asymptomatic disease and, due to the possibility of progressing with complications, one must think preemptively in order to predict earlier diagnoses so that one can intervene in cases of need and avoid unfavorable outcomes.